Periodontal disease as a risk factor for coronary artery disease - Kanaparthy, Rosaiah; Kanaparthy, Aruna (International Journal of Research in Medical Sciences, 2017)
Background: To evaluate and compare the serum levels of total cholesterol, triglycerides and LDL in subjects with healthy periodontal disease with that of chronic generalized severe periodontitis. Methods: 30 subjects with a healthy periodontium (control group) and 30 subjects suffering from chronic generalized severe periodontitis (test group) were selected for the study to compare their serum levels of total cholesterol, triglycerides and LDL after obtaining informed consent. Blood samples were collected and sent for the assessment of lipid (total cholesterol, triglyceride, LDL) levels and the data was subjected to statistical analysis. Results: The results of the our study show that there is significantly higher levels of total cholesterol, triglycerides and LDL in chronic generalized severe periodontitis as compared to healthy periodontium. Conclusion: The observation of this study was that there was a statistically highly significant level of total cholesterol, triglyceride and LDL in chronic generalized severe periodontitis as compared to healthy subjects suggesting a relationship between periodontitis and cardiovascular disease.